Beyond face value the dynamics of talent-talent manager-advertising agency-client power relations in the production of shampoo and soap television commercials - Celades, Recelo Gerasmio; Santos, Josefina M.C. (Quezon City College of Mass Communication University of the Philippines Diliman, 2010)
Beyond face value is qualitative study on the influential power relations that determine the employment of TV commercials talents. As the title suggests, this study literally involve examining facial and physical characteristics of commercial talents critical in their employment or shampoo and soap TV advertisements. True to its title, this study went beyond describing the processes involved in the selection of commercial talents. Using the political economy of communication,it analyzed how existing structures of power affected the decision-making capabilities of the key players, namely, talent, talent manager, advertising agency and client The existing power relations were influenced by culture,market, industry and legal factors. Any behavior from any of the players in the selection process was tempered by these factors. Intensive interviews, participant and unobtrusive observations and recollection of personal experiences were the methods used to gather data. Through convenience sampling, 35 key informants were able to share vital information. Based on the responses of the 35 informants, this study concludes that the hierarchy of powers in the hiring process of TV commercial models is mainly structured as client - advertising agency- talent manager/agency-talent. Although there wereseven combinations of power relations analyzed in this study,in any of these combinations, the existing inequalities f these relations only served to profit the client most and less with the other players.
Thesis (M.S. Media Studies - Broadcasting)--University of the Philippines Diliman
Keywords: Television commercials